Caracterización de la depresión atípica en un adolescente del cantón Vinces - Palacios Barco, Nadia Noemí (2023)
This study focuses on atypical depression in adolescents from the Vinces canton, highlighting the importance of exploring this depressive variant in a specific context. The main objective is to identify and characterize its manifestations in an 18-year-old adolescent. The methodology includes descriptive research, qualitative approach, documentary review and deductive method. Descriptive research allows for the collection of detailed data on atypical depression in adolescents, while the qualitative approach explores subjective experiences, considering cultural and social influences. The documentary review provides a solid theoretical framework to the study. The results indicate that atypical depression is characterized by emotional reactivity, loss of appetite, weight loss, hypersomnia, and a feeling of heaviness in the extremities. Additionally, a clinical interview revealed unexplained restlessness, social isolation, and sadness. These findings are crucial for diagnosis and treatment, highlighting the importance of considering specific symptoms when addressing atypical depression, which can improve patient care. It is emphasized that the manifestations vary, underlining the relevance of the clinical interview in the professional approach. This knowledge benefits the vulnerable population in the Vinces canton.